PEMBENTUKAN, PELATIHAN DAN PEMBERDAYAAN KADER GENSMART BERBASIS TEKNOLOGI DIGITAL DAN WORKSHOP PRODUK ILMIAH “COKELAT CERDAS SEHAT” UNTUK MENINGKATKAN KESEHATAN MENTAL DAN REPRODUKSI REMAJA DI DESA DELOD PEKEN, TABANAN - Rahayuni, I Gusti Ayu Rai; Sagitha, I Gede Edy; Nuartini, Ni Nyoman (Jurnal Abdi Insani, 2025)
Adolescence is a critical period prone to mental and reproductive health challenges. Delod Peken Village, Tabanan, faces difficulties in empowering adolescent health cadres, low awareness of early detection of mental and reproductive disorders, and limited innovative products supporting healthy lifestyles. This community service program aimed to develop an active adolescent cadre community and enhance understanding of mental and reproductive health through digital technology-based interventions and the creation of innovative products. The program was implemented through the formation and training of adolescent cadres in collaboration with health professionals and village components, conducted via workshops, socialization sessions, and continuous mentoring. Results indicated improved knowledge and skills among cadres in the early detection of mental and reproductive health issues, enhanced quality of adolescent posyandu services, and the development of innovative healthy chocolate products made from natural ingredients, scientifically supporting mental and reproductive health and serving as a nutrition education medium. Production tools and materials were provided to ensure sustainability. This initiative also established a safe space for adolescents to mutually support one another while promoting healthy behaviors. Program sustainability is maintained through integration with UPTD Puskesmas Tabanan III and utilization of digital platforms for ongoing monitoring, cadre capacity building, and increased adolescent awareness of mental and reproductive health. This simple, practical, and replicable model can be adapted in other villages with local modifications and multi-sectoral support, offering broad benefits for adolescent and community health.